Effectiveness and Efficiency of the Application of Robotic Process Automation - Nugraha, Erwan; Irjayanti, Maya (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Implementing Robotic Process Automation (RPA) in the shipment handling process at the State-Owned Indonesian Logistics Service Provider (LSP) aims to improve operational effectiveness and efficiency. However, errors in delivery using RPA have been found, resulting in reduced customer satisfaction. These errors are generally related to incorrect shipment data obtained from the website. Therefore, this study focuses on evaluating the effectiveness and efficiency before and after the implementation of RPA. This study aims to analyze the impact of Robotic Process Automation (RPA) on the effectiveness and efficiency of company operations before and after the implementation of RPA at the State-Owned Indonesian Logistics Service Provider, particularly at the Central Post Processing Office. The method used in this study is a qualitative approach. Data was collected from websites related to delivery errors and through observation of the operational department at the State-Owned Indonesian Logistics Service Provider. The analysis was conducted by comparing the level of operational effectiveness and efficiency before and after the implementation of RPA to identify whether the implementation of RPA was in line with the company's expectations. The contribution of this research is to provide insights for State-Owned Indonesian Logistics Service Provider in improving the performance of the RPA system and designing improvement strategies to overcome existing challenges. It is recommended that the State-Owned Indonesian Logistics Service Provider continues to evaluate and develop the RPA system, including improving data quality and integrating supporting technologies to minimize delivery errors and increase customer satisfaction.